2013
DOI: 10.1155/2013/743504
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and Respiratory Effect of Yogic Slow Breathing in the Yoga Beginner: What Is the Best Approach?

Abstract: Slow breathing increases cardiac-vagal baroreflex sensitivity (BRS), improves oxygen saturation, lowers blood pressure, and reduces anxiety. Within the yoga tradition slow breathing is often paired with a contraction of the glottis muscles. This resistance breath “ujjayi” is performed at various rates and ratios of inspiration/expiration. To test whether ujjayi had additional positive effects to slow breathing, we compared BRS and ventilatory control under different breathing patterns (equal/unequal inspiratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
74
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 30 publications
7
74
0
2
Order By: Relevance
“…Mason et al (19) recently reported a series of experiments with yoga beginners where they tested 6/minute breathing with both identical (5:5) and 3:7 inspiration-expiration ratios. The baroreflex sensitivity in their healthy subjects was practically identical during these maneuvers (19). Our study confirms their observations and extends the results to the inverse ratio, (7:3) inspiration-expiration pattern.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Mason et al (19) recently reported a series of experiments with yoga beginners where they tested 6/minute breathing with both identical (5:5) and 3:7 inspiration-expiration ratios. The baroreflex sensitivity in their healthy subjects was practically identical during these maneuvers (19). Our study confirms their observations and extends the results to the inverse ratio, (7:3) inspiration-expiration pattern.…”
Section: Discussionsupporting
confidence: 90%
“…This question is important with regards to the autonomic reflex testing and also to the therapeutic breathing practices but there are very few publications dealing with this issue (5,19). Our goal was to therefore assess the hemodynamic and autonomic responses in healthy volunteers to three breathing exercises with the same slow frequency, but different patterns of inspiratory and expiratory rates.…”
mentioning
confidence: 99%
“…Additionally, previous studies showed evidence of the beneficial properties of yoga in treating various diseases, including cardiovascular disorders, various types of cancers, back pain, and immune dysfunctions, as well as psychological disorders, such as anxiety or depression. [7][8][9][10] Regarding the physiologic condition, yoga practice not only can improve muscular efficiency, endurance time, and enhancement of aerobic exercise capacities but also can reduce perception of exhaustion after exertion caused by physical exercise. 11,12 In addition, yoga is widely used to alleviate mental stress via modulation of hypothalamuspituitary-adrenal axis activation.…”
Section: Introductionmentioning
confidence: 99%
“…The changes were attributed to the inhibitory signals generated during the process of pranayama from cardiorespiratory system leading to modulation of autonomic system resulting in parasympathetic dominance. Heightened baroreflex sensitivity and improved oxygenation have been the proposed underlying mechanisms for the decreased heart rate, systolic blood pressure, and improved oxygen consumption observed in the study [28]. Brown and Gerbarg in a review reported that yoga-breathing interventions increase HRV, improve sympathovagal balance, and promote stress resilience.…”
Section: Discussionmentioning
confidence: 91%